Sterilization methods for humam teeth - MONTEIRO,Rafael Jordão Storino Vaz (2020)
ABSTRACT Appropriate sterilization methods for dental substrate are necessary so that extracted teeth can be used in laboratory activities, since potentially pathogenic microorganisms may be present even if teeth have been cleaned. Objective Evaluating the sterilization process of human teeth performed by microwave irradiation and autoclave sterilization. Methods Fifty human premolar teeth were sectioned in two portions and distributed in two test groups: G1 - autoclave sterilization for 20 minutes, 1Kgf/cm2, at 127ºC; G2 - Microwave irradiation in a recipient containing 100ml of distilled water, 900W for 5 minutes. Before and after the decontamination process, all teeth were immersed in Brain Heart Infusion (BHI) broth to verify their contamination (positive control) and decontamination potential respectively. Results The statistical analysis of the Friedman test (p <0.05) showed that all the tested sterilization methods were statistically effective. Conclusion These results show that both autoclaving and microwave irradiation are effective alternatives for the sterilization of human teeth.